3, 7-Diaryl substituted 10-butylphenoxazines as new hole transporting materials for organic light emitting devices. (February 2017) - Sipaviciute, D.; Tavgeniene, D.; Krucaite, G.; Volyniuk, D.; Grazulevicius, J.V.; Yao, B.; Xie, Z.; Zhang, B.; Grigalevicius, S.
Abstract: Phenyl, naphthyl or vinylphenyl substituted 10-butylphenoxazines were synthesized by a multi-step synthetic rout. The materials were examined by various techniques including thermogravimetry, differential scanning calorimetry, electron photoemission spectroscopy and time of flight method. The materials were found to show adequate thermal stability having initial thermal degradation temperatures in the range of 280–310 °C. Glass transition temperatures of the low-molar-mass materials were in the rage of 31–65 °C. The electron photoemission spectra of thin layers of the derivatives showed low ionization potentials of 5.1–5.15 eV. Hole drift mobilities in thin layers of some derivatives exceeded 2 × 10 −4  cm 2 V −1 s −1  at an electric field of 4 × 10 5  Vcm −1 s at room temperature. These materials have been tested as hole transporting layers in electroluminescent bilayer OLEDs with Alq3 as the emitter. The device with hole transporting layer comprised of 10-butyl-3, 7-di(1-naphthyl)phenoxazine exhibited the best overall performance with very low turn-on voltage of 3.6 V, a maximum luminance efficiency of 2 cd/A and maximum brightness of about 7420 cd/m 2 . Highlights: 3, 6-Diaryl substituted 10-butylphenoxazines were synthesized and characterized. The derivatives are efficient materials for electroluminescent OLEDs. Hole drift mobility in their layers exceed 2 × 10 −4  cm 2 V −1 s −1 . OLED device using one the materials demonstrated efficiency of 2 cd/A.